2011
DOI: 10.1039/c0cc05353h
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the alkali cation on the mechanism of the electro-oxidation of ethylene glycol on Pt

Abstract: By means of in situ IR spectroscopy we investigate the effect of dissolved alkali cations on the electro-oxidation of ethylene glycol on platinum in alkaline media. The results revealed that the increase in the oxidation currents (Li(+) < Na(+) < K(+)) is reflected in the increase in the ratio between carbonate and oxalate produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 18 publications
4
56
0
4
Order By: Relevance
“…3,4 Nonspecifically adsorbed cations are known to affect the catalytic activity of fuel cell reactions through noncovalent interaction. 5,6 Noncovalent interactions between adsorbed and nonadsorbed species often result in a structural gap between electrochemical and ultrahigh vacuum (UHV) conditions. 7,8 Thus, weak interactions, such as hydrogen bonding and electrostatic forces, affect adsorbed layer stability and electrochemical reactions significantly.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Nonspecifically adsorbed cations are known to affect the catalytic activity of fuel cell reactions through noncovalent interaction. 5,6 Noncovalent interactions between adsorbed and nonadsorbed species often result in a structural gap between electrochemical and ultrahigh vacuum (UHV) conditions. 7,8 Thus, weak interactions, such as hydrogen bonding and electrostatic forces, affect adsorbed layer stability and electrochemical reactions significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Although an improved understanding and optimization of the interactions between covalently-bonded reaction intermediates is significant for future advances in electrocatalysis, an even more exciting subject that is at the frontier of current surface electrochemical knowledge relates to how solvated, non-specifically adsorbed ions located in the vicinity of the surface may influence the chemistry of covalently-adsorbed reactive and spectator species [9,15,[23][24][25][26][27][28]. It has recently been shown that these solvated ions can modify the surface in a variety of ways; e.g., via direct energetic interaction with covalentlyadsorbed species or via the formation of non-specifically & Nenad M. Markovic nmmarkovic@anl.gov adsorbed patterns of ion/water complexes that selectively control the reactivity of electrochemical interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Besides the search for new alloy materials,s pecial attention has been paid to the effect of the composition of the electrolyte. [5][6][7][8][9][10][11] In acidic media, among all metals,P ta nd Pd are the metal catalysts of choice for the oxidation of many organic molecules. Also, the search for suitable alloys with higher catalytic activity is mainly based on Pt alloys, including metals such as Bi, [12][13][14][15] Pb, [16,17] Sn, [18,19] or Mo, [20,21] among others, in the matrix.…”
Section: Introductionmentioning
confidence: 99%